Glimpses of Quranic expression in Surat Al-Maarij (Journal of the College of Basic Education, 2025)
The content of this study focuses on shedding light on one of the chapters of the Hoiy Quran , namely the biessed Surah Al-Maarij . The study explores various scientific and epistemological aspects of this Surah , not limiting itself to a single perspective . Rather , it extends to include Surah Al-Maarij along with other Quranic chapters such as Abasa and Al-Qariah highlighting the common expressive and interpretative meanings among these Surahs . This research is divided into two section , each containing multiple topics that discuss different aspects of the blessed Surah and elucidate its rhetorical and aesthetic features in Quranic expression .